Orange Peel Extracts: Chemical Characterization, Antioxidant, Antioxidative Burst, and Phytotoxic Activities. (2nd September 2016) - Erukainure, Ochuko L.; Ebuehi, Osaretin A.T.; Iqbal Chaudhary, M.; Mesaik, M. Ahmed; Shukralla, Ahmed; Muhammad, Aliyu; Zaruwa, Moses Z.; Elemo, Gloria N.
ABSTRACT: The search for novel drugs and alternative medicine has led to increased research in medicinal plants. Among such plants is the orange fruit. Its peels have been utilized for long as an active ingredient in most traditional medicines. This study aims at investigating the chemical properties of the hexane and dichloromethane (DCM) extracts of orange peel as well as their biological potentials. Blended peels were extracted with n-hexane and n-dichloromethane, respectively. The resulting extracts were subjected to gas chromatography mass spectrometry (GCMS) characterization. The extracts were also assayed for free radical scavenging ability against 1, 1 –diphenyl –2 picrylhydrazyl (DPPH), antioxidative burst via measuring luminol –amplified chemiluminescence response in human blood, and phytotoxicity against lemna minor . GCMS analysis revealed a predominance of fatty acid methyl esters in the hexane extract, while the DCM extract had more ketone metabolites. The DCM extract had significant ( p < .05) higher free radical scavenging and antioxidative burst activities compared to the hexane. Both extracts revealed a significantly ( p < .05) high phytotoxicity activity. Results from this study indicated that solvent type played a vital a role in the extraction of secondary metabolites, which are responsible for the observed biological activities. The higher activities by the DCM extract can be attributed to its constituents as revealed by GCMS analysis. There is great need to explore the phytotoxicity potentials of both extracts as natural herbicides.